2017
DOI: 10.7759/cureus.1004
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Myeloperoxidase as a Biomarker for Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is a chronic condition involving the inflammation of the colon and small intestine. IBD affects as many as 1.4 million people in the U.S. alone and costs the health care industry over $1.7 billion annually. Managing IBD normally requires invasive and often discomforting diagnostic tests. In an effort to alleviate the painful and costly nature of traditional diagnosis, there has been increasing research initiative focused on noninvasive biomarkers. PubMed, provided by the United… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 29 publications
1
73
0
Order By: Relevance
“…Neutrophils often exert pro-inflammatory functions at sites of inflammation ( 71 , 72 ), and a neutrophil-derived protein, myeloperoxidase, is widely used as a marker of colitis severity in IBD ( 73 75 ). Therefore, we investigated the cellular mechanisms contributing to elevated numbers of neutrophils in DSS-treated LysMCre;Arnt fl / fl mice.…”
Section: Resultsmentioning
confidence: 99%
“…Neutrophils often exert pro-inflammatory functions at sites of inflammation ( 71 , 72 ), and a neutrophil-derived protein, myeloperoxidase, is widely used as a marker of colitis severity in IBD ( 73 75 ). Therefore, we investigated the cellular mechanisms contributing to elevated numbers of neutrophils in DSS-treated LysMCre;Arnt fl / fl mice.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, myeloperoxidase (MPO) whose activity is assessed during evaluation of intestinal ischemic injury, was shown to be an enzyme released due to neutrophil activation and is present during the production of free oxygen radicals [15,16]. Various studies have demonstrated that increase in MPO activity as a sign of neutrophil infiltration during mesenteric I/R injury causes endothelia dysfunction and inflammation [17,18].…”
Section: Discussionmentioning
confidence: 76%
“…S1H, S1I, S1J, and S1K). MPO production is often increased in the colon of IBDs patients [24]. Similarly, DSS drastically elevated the MPO concentration in the colon of mice, but such an elevation was signi cantly dampened by oral EGCG (Fig.…”
Section: Oral But Not Rectal Administration Of Egcg Alleviates Dss-mentioning
confidence: 82%